2022
DOI: 10.1002/admt.202200219
|View full text |Cite
|
Sign up to set email alerts
|

High Strength and High Wear‐Resistant Ti Composites Fabricated by Powder Metallurgy Pressureless Sintering

Abstract: In this work, high strength and high wear‐resistant titanium matrix composites (TMCs) reinforced with in situ TiC derived from pyrolysis of polysilazane (PSZ) are fabricated successfully. The processing technology is developed with a novel powder metallurgy method combining solution‐assisted wet mixing and pressureless sintering. The effects of PSZ addition on the microstructure, hardness, mechanical properties, and tribological properties are systematically studied. The TMCs possess better comprehensive prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…With the ongoing development of metal matrix composites, titanium-based composites have emerged as a promising material, boasting high strength, excellent ductility, remarkable wear resistance, and superior high-temperature durability. These exceptional properties have led to their widespread application in aerospace and advanced military fields [1][2][3]. Unfortunately, research has revealed that the majority of titanium matrix composites currently feature a uniform distribution of reinforcement within the matrix material, leading to subpar mechanical properties and serious ambient temperature brittleness [4].…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing development of metal matrix composites, titanium-based composites have emerged as a promising material, boasting high strength, excellent ductility, remarkable wear resistance, and superior high-temperature durability. These exceptional properties have led to their widespread application in aerospace and advanced military fields [1][2][3]. Unfortunately, research has revealed that the majority of titanium matrix composites currently feature a uniform distribution of reinforcement within the matrix material, leading to subpar mechanical properties and serious ambient temperature brittleness [4].…”
Section: Introductionmentioning
confidence: 99%